Pengelolaan Diri dan Regulasi Emosi dengan Pendekatan Dialectical Behavior Therapy (DBT) Kelompok pada Gangguan Mood - Salma Ghina Sakinah Safari; Yudiana Ratnasari; Isabella Sasqia Mulya (Guidena)
Various interventions have been researched that are capable of reducing symptoms of mood disorders, including DBT (Goldstein et al., 2015; Van Dijk et al., 2013). In addition to individual interventions, group therapy interventions have also been widely used and proven to be effective in reducing symptoms of Bipolar disorder in participants (Costa et al., 2012; Rebeca et al., 2020). This study aims to examine the effectiveness of group therapy using a DBT approach on the emotional regulation and self-control of individuals with mood disorders. Group therapy was conducted on ten individuals with mood disorders. The Brief Self-Control Scale and Mindfulness Attention Awareness Scale were used as tools for quantitative data collection. Meanwhile, observation and interviews were conducted to assess group therapy's effectiveness qualitatively. The hypothesis testing results indicate no significant correlation between the two variables. These findings are helpful for the development of psychological interventions for individuals with mood disorders in Indonesia.